TNF-α sensitizes chemotherapy and radiotherapy against breast cancer cells. Issue 1 (December 2017) - Wu, Xiao; Wu, Meng-Yao; Jiang, Min; Zhi, Qiaoming; Bian, Xiaojie; Xu, Meng-Dan; Gong, Fei-Ran; Hou, Juan; Tao, Min; Shou, Liu-Mei; Duan, Weiming; Chen, Kai; et al.
Abstract Purpose Despite new developments in cancer therapy, chemotherapy and radiotherapy remain the cornerstone of breast cancer treatment. Therefore, finding ways to reduce the toxicity and increase sensitivity is particularly important. Tumor necrosis factor alpha (TNF-α) exerts multiple functions in cell proliferation, differentiation and apoptosis. In the present study, we investigated whether TNF-α could enhance the effect of chemotherapy and radiotherapy against breast cancer cells. Methods Cell growth was determined by MTT assay in vitro, and by using nude mouse tumor xenograft model in vivo. Cell cycle and apoptosis/necrosis were evaluated by flow cytometry. DNA damage was visualized by phospho-Histone H2A.X staining. mRNA expression was assessed by using real-time PCR. Protein expression was tested by Western blot assay. Results TNF-α strengthened the cytotoxicity of docetaxel, 5-FU and cisplatin against breast cancer cells both in vitro and in vivo. TNF-α activated NF-κB pathway and dependently up-regulated expressions of CyclinD1, CyclinD2, CyclinE, CDK2, CDK4 and CDK6, the key regulators participating in G1→S phase transition. As a result, TNF-α drove cells out of quiescent G0/G1 phase, entering vulnerable proliferating phases. Treatment of TNF-α brought more DNA damage after Cs137 -irradiation and strengthened G2/M and S phase cell cycle arrest induced by docetaxel and cisplatin respectively. Moreover, the up-regulation of RIP3 (a necroptosis marker) by 5-FU, and the activation of RIP3 by TNF-α, synergistically triggered necroptosis (programmed necrosis). Knockdown of RIP3 attenuated the synergetic effect of TNF-α and 5-FU. Conclusion TNF-α presented radiotherapy- and chemotherapy-sensitizing effects against breast cancer cells.